Alerta emprendedora y conocimiento previo para la identificación de oportunidades emprendedoras: El papel moderador de las redes sociales - Matilde Ruiz-Arroyo; Ignacio Sanz-Espinosa; María del Mar Fuentes-Fuentes (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2015)
– The present study advances in the research about identification of entrepreneurial opportunities, by analyzing the moderating effect that social network's size and strength may have on the relationship of prior knowledge and alertness with opportunity identification. We draw on a sample made up of 199 Andalusian entrepreneurs to perform a regression analysis. The results show a negative influence of prior knowledge on the number of identified opportunities, as well as a positive moderating effect of network strength over the relationship between alertness and opportunity identification. Our work can contribute to the entrepreneurship literature, given that we integrate in a model the effects of alertness, prior knowledge and social capital on the study of the opportunity identification phase, by applying a contingent perspective based on the moderating role of certain networks' characteristics.
Keywords: M19; L26; 330; Opportunity identification; Prior knowledge; Entrepreneurial alertness; Social networks; Entrepreneurial process